Prevalence of alpha actinin-3 gene (ACTN3) R577X and angiotensin converting enzyme (ACE) insertion / deletion gene polymorphisms in national and amateur Turkish athletes - ULUCAN, KORKUT (C M B ASSOC, 2018)
Studies to date showed the importance of alpha- actinin-3 (ACTN3) R577X and angiotensin converting enzyme (ACE) ID polymorphisms on determining athletic performance. Therefore, in this study, we aimed to examine polymorphisms given to Turkish athletes and compare them with sedentary individuals. Genomic DNAs were extracted from peripheral blood by using commercially available DNA isolation kit (Macherey-Nagel, NucleoSpin (R), Germany). For this study, a total of 84 volunteers (23 national athletes, 27 amateur athletes and 34 sedentary controls) was recruited. ACE ID genotypes were determined by conventional polymerase chain reaction, and ACTN3 R577X polymorphisms by polymerase chain reaction- restriction fragment length polymorphism methodology. In ACTN3 R577X polymorphism, RX was the dominating genotype, and we detected no RR genotype in national athletes. (no RR genotype was detected in national athletes) X allele is more frequent in national athletes and R allele was more frequent in both amateur athletes and control group. II genotype was more frequent in national athletes and in control group, whereas DD genotype was more frequent in amateur athletes for ACE ID polymorphism. When we consider alleles, D allele was found more frequently in amateur athletes and control group whereas I allele was more frequent in national athletes in ACE ID polymorphism. For ACTN3, X allele was superior to R allele. ACTN3 R577X and ACE ID polymorphisms were important biomarkers in determining athletic performance. However, our results in Turkish athletes suggest that ACE D allele and ACTN3 X alleles may be beneficial to athletes potentially, regardless of the distance they perform.
Keywords: Sports; Genetics; Athletic performance; Athlete; ALPHA-ACTININ-3 GENE; PERFORMANCE; GENOTYPE